2007
DOI: 10.1123/ijsnem.17.6.521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein-Rich Feeding on Recovery after Intense Exercise

Abstract: Carbohydrate ingestion after prolonged strenuous exercise enhances recovery, but protein might also be important. In a crossover with 2-wk washout, 10 cyclists completed 2.5 h of intervals followed by 4-h recovery feeding, provided 218 g protein, 435 g carbohydrate, and 79 g fat (protein enriched) or 34 g protein, 640 g carbohydrate, and 79 g fat (isocaloric control). The next morning, cyclists performed 10 maximal constant-work sprints on a Velotron cycle ergometer, each lasting approximately 2.5 min, at appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…The numerical value for each verbal anchor was not displayed on the scale charts, so as not to distract the participant from their rating, as the numerical value increased factorially in accordance with the CR10 scale by x 1.6 . The CR10 scale used to construct the psychometric scales for this study has previously been shown to be reliable and valid (4) and the CVs for most markers on the present scales ranged from 0.20 to 0.96 of a scale unit (35).…”
Section: Psychometric Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical value for each verbal anchor was not displayed on the scale charts, so as not to distract the participant from their rating, as the numerical value increased factorially in accordance with the CR10 scale by x 1.6 . The CR10 scale used to construct the psychometric scales for this study has previously been shown to be reliable and valid (4) and the CVs for most markers on the present scales ranged from 0.20 to 0.96 of a scale unit (35).…”
Section: Psychometric Scalesmentioning
confidence: 99%
“…Participants were given a verbal countdown in preparation for the start of each sprint and at 20, 10, 5, and 2 kilocalories to go in preparation for the end of each sprint. Test characteristics are described elsewhere (35). During the performance test, psychometric data and blood was collected immediately following sprints 1, 4, 7, and 10.…”
Section: Protocolsmentioning
confidence: 99%
“…Findings have been intriguing with some, but not others [118,119], reporting enhanced TTE [120,121,122] and TT performance [123] with during-exercise CHO-PRO versus CHO intake alone. Additionally, some, but not all [124,125,126,127,128,129,130], studies investigating the effects of post-exercise CHO-PRO intake on subsequent exercise performance have also noted enhanced TTE [131,132] and TT performance [133], possibly as a result of increased glycogen resynthesis [127,134,135,136]. Despite these findings, there has been very little research done analyzing the effects of pre-exercise CHO-PRO in the performance context.…”
Section: Mixed Cho-protein Mealsmentioning
confidence: 99%
“…Four studies that evaluated the effects of a 2:1 ratio on cycling performance were inconclusive. [60][61][62][63] A 2006 study reported no difference in total distance cycled with supplementation, but two years later the same group reported the effect was significant. 60 61 Similarly, another group found added protein improved sprint cycling performance in men 60 hours after exercise but not at 15 hours after exercise.…”
Section: What the Evidence Saysmentioning
confidence: 99%